Pemilihan Prediktor Delisting Terbaik (Perbandingan Antara The Zmijewski Model, The Altman Model, dan The Springate Model) - Syamsul Hadi; Atika Anggraeni (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2008)
This research objective is to know the best delisting predictor in IDX. There are three famous bankruptcy predictors namely The Zmijewski Model, The Altman Model, and The Springate Model. This research uses these three models to predict delisting.This research took IDX delisting data for 2003 – 2007 except banks. To have a good comparison, this research took same number of non-delisting companies which are in the same category randomly. This research use logistic regression of Microsoft Excel. This research found that The Zmijewski Model could not predict delisting. Both The Altman Model and The Springate Model could predict delisting moderately. The Altman Model is the best delisting predictor.Keywords: Delisting, The Zmijewski Model, The Altman Model, The Springate Model.